Christianization of Kievan Rusʼ in the context of European Middle Ages - Fiadosik, Victar A. (Journal of the Belarusian State University. History, 2018)
This article examines the Christianization of Kievan Rusʼ in the context of Medieval European political and religious history. It aims at comparative analysis of Christianity development in Western Europe and Byzantium in the Early and High Middle Ages with the specific focus on comparative analysis of the beginning of the Christianization process in Scandinavia and Kievan Rusʼ. The article explores the role of the «Normanʼs factor» in the Christianization of the Kievan Rusʼ. It claims that Byzantium was a powerful cultural model for Eastern Slavs, and Christianity gave them the opportunity to share the cultural heritage of Antiquity. But, qualitatively, this was a late-antique and Christian heritage. By using the example of the medieval Christian «four kingdoms» doctrineʼs role in the history of mankind, the article shows that the concepts of Greek polis and Roman civitas were lost in this heritage. By using evidence from «Povest Vremmenykh Let» («Tale of Bygone Years») the article argues that Kievan Rusʼ did not perceive Western Christianity as a threat and many contradictions between the Byzantine and Roman churches were not understood or heeded by the Christians of Kievan Rusʼ.